Implementation Plan in Response to The Executive Board-Endorsed Categorization of Open Actions in Management Implementation Plans. (Policy Papers; Policy Paper ;, 2022)
This management implementation plan (MIP) proposes eight reformulated actions that would benefit from further follow up, in line with the Board-approved Categorization of Open Actions in MIPs. The MIP aims to strengthening the continuity of the relationship between the Fund and member countries, enhancing knowledge sharing across successive country teams, improving incentives for sound data management, alleviating country authorities' concerns about disclosure, and creating a more robust review process for working papers.